High throughput mating tests in Neurospora crassa - Kevin McCluskey; Rachel L. Yedlin; Sheera A. Walker (Fungal Genetics Reports, 2006)
Mating type tests in Neurospora crassa can be laborious and tedious. Since we were arraying mutants for distribution, we have developed a method to carry out mating type tests in 96-well plates. This technique is highly efficient and reproducible and gives results in three to four days.